Between Form and Molecule: Investigating the Beyond in Chris Colfer’s The Wishing Spell - Zainab Akram (NUML Journal of Critical Inquiry)
Fairy tales permeate the world with a magical charm, but time has brought changes in fairy tale narration, mode, context and interpretations. Under the post structural lens, the undertaken research investigates the transformations that occur at molecular level, beyond the physical and molar corporeality among selected characters in the fairy tale, The wishing spell (2013). The focus is not the examination of changes in physical anatomic structure or form of the selected characters, rather the exploration of body’s capability and potentials of undergoing phenomenological transformations through the lens of becoming molecular by Gilles Deleuze and Felix Guattari (1987). Becoming molecular promotes the idea that instead of comprehending the whole form of an issue, a fragment or molecule needs to be comprehended as it makes it easy to understand the entire form of problem. Becoming molecular is an internal or mind attachment of the body to another entity and the attachment or link is beyond the physical form of corporal state of being. The undertaken research endeavors to map multiple occurrences of becoming molecular in the characters of Snow White and the Evil Queen, by following the thematic model of textual analysis by Miles and Huberman (2014). The findings reveal that becoming molecular is an endless process that emerges in unlimited molecular links amid two different bodies. These links illuminate profound insights by influencing thoughts and bringing changes in actions and behavior. The changes cannot be perceived through senses as in the physical world. These links do not disrupt the physical appearance of either body, rather bring changes at molecular level.